Effects of Bonding Parameters on Free Air Ball Properties and Bonded Strength of Ag-10Au-3.6Pd Alloy Bonding Wire - Cao, Jun (Micromachines (Basel), 2020)
Free air ball (FAB) and bonded strength were performed on an Ag-10Au-3.6Pd alloy bonding wire (diameter of 0.025 mm) for different electronic flame-off (EFO) currents, times and bonding parameters. The effects of the EFO and bonding parameters on the characteristics of the FAB as well as the bonded strength were investigated using scanning electron microscopy. The results showed that, for a constant EFO time, the FAB of the Ag-10Au-3.6Pd alloy bonding wire transitioned from a pointed defined ball to an oval one, then to a perfectly shaped one, and finally to a golf ball with an increase in the EFO current. On the other hand, when the EFO current was constant and the EFO time was increased, the FAB changed from a small ball to a perfect one, then to a large one, and finally to a golf ball. The FAB exhibited the optimal geometry at an EFO current of 0.030 A and EFO time of 0.8 ms. Further, in the case of the Ag-10Au-3.6Pd alloy bonding wire, for an EFO current of 0.030 A, the FAB diameter exhibited a nonlinear relationship with the EFO time, which could be expressed by a quadratic function. Finally, the bonded strength decreased when the bonding power and force were excessively high, causing the ball bond to overflow. This led to the formation of neck cracks and decrease in the bonded strength. On the other hand, the bonded strength was insufficiently when the bonding power and force were small. The bonded strength was of the desired level when the bonding power and force were 70 mW and 0.60 N (for the ball bonded) and 95 mW and 0.85 N (for the wedge bonded), respectively.